Entrepreneurship Education and Training - Sanchez-Garcia, Jose C. (IntechOpen, 2015)
Entrepreneurship has a tremendous impact on the economic development of a country, so much that entrepreneurship is seen as a solution for the fast changing economic demands worldwide and has been recognized as a path to sustainable economic development. Despite recognition of entrepreneurship on the road to global economic development, a large body of research on the elements of entrepreneurship education remains unresolved. Are these behaviors inherent to human beings, their genetic code, their psychological traits, or can students, young children, and even adults, be taught how to become an entrepreneur? This book presents several chapters following different approaches to answer these questions. Researchers explore education programs in different countries, they show experiences in entrepreneurship education, explain how to teach entrepreneurial skills, cultural issues, and propose some orientations and reflections on entrepreneurship education.